The Impact of Credit Risk Management on the Performance of Financial Institutions in Uganda - Joshua Mukhwana (My University, 2023)
The study examined the effect of credit risk management on financial performance of Housing Finance Bank. The Specific Objectives of the study were to examine the effect of Credit Risk identification, Credit Risk assessment and Credit Risk control on the financial performance of HFB. The study used a descriptive cross-sectional design using both qualitative and quantitative approach to collect data from a sample of 59 respondents. Questionnaire and interviewing guides were used to collect the data. Quantitative data was analyzed using measurement of central tendency and qualitative data was analyzed using correlations and regression analysis techniques. The study found a high positive significant relationship between credit risk identification and financial performance. The study also found a high positive significant relationship between credit risk assessment and financial performance. Then the study found a high positive significant relationship between credit risk control and financial performance The study concluded that effective credit risk management through risk identification, assessment and control in financial institutions if well managed has a resultant significant positive effect on the financial performance of the bank and vice versa. The study recommends that to achieve the desired sales revenue and profitability, financial institutions should be guided by a philosophy of continuously exploring all possible risk origins and their classification to guide credit risk assessment; continuously exploring existing and incidental credit risk data and risk estimation using industry best responsive credit risk estimation models/techniques; review and strengthen the credit mitigation and monitoring mechanism through continuous training and allocations of necessary resources for the credit recovery team.